Aetiology, diagnosis, and clinical management of vulvodynia - Vasileva, Polina (Prz Menopauzalny, 2020)
Chronic vulvar pain or discomfort for which no obvious aetiology can be found, i.e. vulvodynia, can affect up to 16% of women, and it may be found in girls and women across all age groups and ethnicities. Most patients describe it as burning, stinging, irritation, or rawness. The symptoms may spread to the whole vulva (generalised vulvodynia) or only to part of it, such as the clitoris (clitorodynia) or the vestibule of the vagina (vestibulodynia). This condition is often underreported and underrecognised by health care providers. Vulvodynia is a significant burden to society, the health care system, the affected women, and their intimate partners. It has a negative impact on quality of life. Vulvodynia is a diagnosis of exclusion with unknown aetiology. The gynaecologist plays a key role in excluding other causes of vulvar pain, and collaborating with other health care providers to manage the patient’s pain. Although many therapeutic options are available, such as vulvar care measures, psychological approaches, local treatment, oral medications, surgical procedures, electrical nerve stimulation, and laser therapy, there is no single treatment effective for all patients. That is why individualised management is needed. An individualised, holistic, and often multidisciplinary approach is needed to effectively manage the patient’s pain and pain-related distress.